From Saturated BN Compounds to Isoelectronic BN/CC Counterparts: An Insight from Computational Perspective. Issue 43 (4th September 2015) - Sagan, Filip; Piękoś, Łukasz; Andrzejak, Marcin; Mitoraj, Mariusz Paweł
Abstract In the present study, the inorganic analogues of alkanes as well as their isoelectronic BN/CC counterparts that bridge the gap between organic and inorganic chemistry are comparatively studied on the grounds of static DFT and Car–Parrinello molecular dynamics simulations. The BN/CC butanes CH3CH2BH2NH3, BH3CH2NH2CH3, and NH3CH2BH2CH3 were considered and compared with their isoelectronic counterparts NH3BH2NH2BH3 and CH3CH2CH2CH3. In addition, systematical replacement of the NH2BH2 fragment by the isoelectronic CH2CH2 moiety is studied in the molecules H3N(NH2BH2)3–m(CH2CH2)mBH3 (for m=0, 1, 2, or 3) and H3N(NH2BH2)2–m(CH2CH2)mBH3 (for m=0, 1, or 2). The DFT and Car–Parrinello simulations show that the isosteres of the BN/CC butanes CH3CH2BH2NH3, BH3CH2NH2CH3, and NH3CH2BH2CH3 and of larger oligomers of the type (BN)k(CC)l where k≥l are stable compounds. The BN/CC butane H3NCH2CH2BH3 spontaneously produces molecular hydrogen at room temperature. The reaction, prompted by very strong dihydrogen bonding NH⋅⋅⋅HB, undergoes through the neutral, hypervalent, pentacoordinated boron dihydrogen complex RBH2(H2) [R=(CH2CH2)nNH2]. The calculations suggest that such intermediate and the other BN/CC butanes CH3CH2BH2NH3, BH3CH2NH2CH3, and NH3CH2BH2CH3 as well as larger BN/CC oligomers are viable experimentally. A simple recipe for the synthesis of CH3CH2BH2NH3 is proposed. The strength of the dihydrogen bonding appeared to be crucial for the overall stability of the saturated BN/CC derivatives.